Catastrophe Containment and Relief Trust-Third Tranche Of Debt Service Relief In The Context Of The COVID-19 Pandemic. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2021)
This paper proposes that the Executive Board approve the disbursement of a third tranche of CCRT debt service relief to 28 of the 29 CCRT-eligible members, covering the period April 14, 2021 through October 15, 2021, given staff's assessment that sufficient financial resources are available.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Lending and Debt Problems